(Re)contextualizando una colección de cráneos: a un siglo de las excavaciones de Julio C. Tello y Alfred Kroeber en Cerro de Oro (550-1600 d.C.), valle de Cañete, Perú - De la Puente-León, Gabriela (2025)
This report aims to present the results of a recontextualisation of a collection of 24 human crania held at the Museo Nacional de Arqueología, Antropología e Historia del Perú, which were originally recovered at the site of Cerro de Oro in 1925. First, the report explains that its name notwithstanding, the collection was actually excavated by Julio C. Tello and not by Alfred Kroeber. Second, the report includes data on the biological profile and the cephalic modifications found in 16 individuals from the of Cerro de Oro occupation (A.D. 550–950). This study aims to preserve the legacy of Tello’s excavations and to show the importance of studying museographical collections. The paper is likewise a contribution to our knowledge of the pre-Hispanic populations of Cerro de Oro insofar as it supplements studies based on more recent excavations.